Perancangan Sistem Informasi Portofolio Dosen di Jurusan Teknik Industri UNS - Nugroho, Kristanto Agung; Iftadi, Irwan; Priyandari, Yusuf (Performa: Media Ilmiah Teknik Industri, 2011)
Portfolio lecturer required for the interests of each faculty and department. Portfolio lecturer required for promotion of faculty and lecturers certification. On the other hand, the portfolio required by the department faculty as an important part in the assessment of accreditation at the majors and is also used to compile Ekuivalensi Nilai Mengajar Penuh (EWMP). In this research, the initial system identification, system design proposal, and then to design the application. Identification of the initial system is to find problems early and identify the needs of the system the desired system, both input and output. The design of the proposed system consists of the design of the proposed system framework, design hardware and software, design development cost structure, and design calculations EWMP value. While the design phase consists of designing application interface and database design. Then, from the design interface is created between the face using the program Visual Basic 2008 and the design of the database created with MySQL database. The results of this study is information systems portfolio based computer that can print EWMP data, supporting the certification process lecturers, support the accreditation process majors, and supporting faculty promotion process. Designed system has a database for storing data and capable of storing a lecturer portfolio data from the KP and TA SIKAPTA databases and applications to enter and retrieve data as needed. Applications can be accessed by multiple users simultaneously via an internet connection. Through computer-based information systems, all lecturers EWMP activity will be recorded neatly, can be traced back and ready to print when needed. In addition, data can be managed more EWMP by lecturers to the process of certification and promotion.